Intracystic Papillary Neoplasm of Gall Bladder: A Case Report - Mallik, Dipendra Kumar; Khanal, Suman; Dhakal, Sunil; Mishra, Roshan; Dhungana, Ishan; Sapkota, Ganga (Nepalese Journal of Cancer, 2019)
Intracystic papillary neoplasm of gallbladder (ICPNG) is defined as macroscopic papillary growth in the gallbladder. We report a case of ICPNG with epigastric metastasis. A 70-year-old woman was referred to our hospital with epigastric mass, with prior history of laproscopic cholecystectomy 15 months before. Post op histopathology report revealed Intracystic papillary neoplasm (premalignant lesion). Microscopic findings state tumor cells arranged in complex papillary pattern with fibrovascular core arising from gall bladder mucosa. Few of the Rokitansky Aschoff sinuses (RAS) also involved by these tumor cells. Adjacent gall bladder mucosa shows pyloric metaplasia. On FNAC of epigastric mass it showed Metastatic carcinoma favoring Adenocarcinoma. In present case, ICPNG was seen with few of Rokitansky Aschoff sinuses. It is necessary to determine appropriate proper surgical approach likely extended cholecystectomy, or pancreaticoduodenectomy to get R0 resection.